Analysis on the Acceptance of COVID-19 Vaccine Administration for Children in Indonesia Based on the Theory of Planned Behavior - Liana Fitriani Hasymi; Nurul Mardiati; Ratih Puspita Kusuma Dewi; Rizal Rizal; Imam Jayanto; Dian Nurmansyah (Sanata Dharma University, 2024)
The administration of COVID-19 vaccine in children aims to control the spread of this disease in Indonesia. Parents make the decision whether to vaccinate their children against COVID-19 or not. This study was conducted to analyze parents’ acceptance of the COVID-19 vaccination for children in Indonesia based on the Theory Planned Behavior (TPB). The research design used a cross-sectional survey involving 400 parents of children aged 6-11 years in Indonesia in 34 provinces. Samples were purposively selected based on inclusion criteria: parents are older than 18 years, parents of children aged 6-11 years and live in Indonesia. The exclusion criteria were parents of children who recovered from COVID-19 less than 3 months and children with COVID-19 contraindications. The chi-squared test was conducted to determine the correlation between parents’ acceptance and TPB constructs that include attitudes, subjective norms and behavioral control. A multivariate logistic regression analysis was employed to analyze the TPB construct with the largest contribution on parents’ acceptance of the COVID-19 vaccination. The results showed high acceptance toward COVID-19 vaccination for children aged 6-11 years (98.5%). Positive subjective norms and positive behavioral control also contributed to the parental acceptance of the COVID-19 vaccine for children in Indonesia (p-value = 0.000), in which subjective norms had the largest influence (sig. 0.096 value with Exp B value of 6.203). TPB is a useful framework in developing proper interventions to raise the vaccination acceptance of parents in Indonesia.